Placenta-Derived Mesenchymal-like Adherent Stromal Cells as an Effective Cell Therapy for Cocaine Addiction in a Rat Model - Hilla Pe'er-Nissan; Hadas Ahdoot-Levi; Oshra Betzer; Pnina Shirel Itzhak; Niva Shraga-Heled; Iris Gispan; Menachem Motiei; Arthur Doroshev; Yaakov Anker; Rachela Popovtzer; Racheli Ofir; Gal Yadid (MDPI AG, 2022)
Recent research points to mesenchymal stem cells' potential for treating neurological disorders, especially drug addiction. We examined the longitudinal effect of placenta-derived mesenchymal stromal-like cells (PLX-PAD) in a rat model for cocaine addiction. Sprague-Dawley male rats were trained to self-administer cocaine or saline daily until stable maintenance. Before the extinction phase, PLX-PAD cells were administered by intracerebroventricular or intranasal routes. Neurogenesis was evaluated, as was behavioral monitoring for craving. We labeled the PLX-PAD cells with gold nanoparticles and followed their longitudinal migration in the brain parallel to their infiltration of essential peripheral organs both by micro-CT and by inductively coupled plasma-optical emission spectrometry. Cell locations in the brain were confirmed by immunohistochemistry. We found that PLX-PAD cells attenuated cocaine-seeking behavior through their capacity to migrate to specific mesolimbic regions, homed on the parenchyma in the dentate gyrus of the hippocampus, and restored neurogenesis. We believe that intranasal cell therapy is a safe and effective approach to treating addiction and may offer a novel and efficient approach to rehabilitation.